PEMODELAN GEOLOGI DAN PERHITUNGAN CADANGAN HIDROKARBON PADA FORMASI GUMAI SERI G-50 LAPANGAN “MALIKA” DENGAN MENGGUNAKAN DATA SUMUR DAN PSEUDO 3D PROVINSI JAMBI, CEKUNGAN SUMATRA SELATAN - Syahnazaina Syahnazaina (Geological Engineering E-Journal, 2013)
MALIKA field located in the Sub - Basin Formation Gumai Jambi , South Sumatra Basin. Geological modeling in this field as an effort in the development field. Application of geological modeling knowledge is now growing rapidly along with the development of software based geology and geostatistics .Geological modeling is purpose to see reservoir characterization from facies geometry patterns , and see the spread of the distribution of porosity, permeability, VSH and Net To Gross ( NTG ) were validated with facies distribution. Value of each property from petrophysical are used to calculate  existing reserves  for reservoir simulation purposes.Modelling on malika field use pseudo 3d, because and  3D modellling correction values higher than 2D. Analysis sequen stratigraphy purposed for determine facies on Malika field. analysis sequen stratigraphy purposed for determine facies on Malika field, whereas  petrophysical properties distribution conducted through from geostatistical approach with use variogram on petrel. For make a model distribution through the creation of as many as 10 realization of the facies distribution, porosity distribution,  VSH distribution and  Net To Gross (NTG). Realization of each model is made in the form of rankings, realization purpose to provide value not too pessimistic nor optimisticFrom sequen stratigraphy, Malika field have 5 zones reservoir sand, that is G-50A(4950-5120ft), G-50B (5035-5170ft), G-51 (5090-5312ft), G-52A (5177 -5353ft) dan G-52B (5221-5430ft). Depositional environment on the shelf until the delta , with reservoir thickness 40–72ft. Volume porosity in each zone has a value ranging from 182 643 ( 103 acre.ft )  and Original Oil In Place ( OOIP ) 192.727.521 .103 STB.